Diagnosis and Prognosis in Idiopathic Normal Pressure Hydrocephalus. (November 2014) - Ghosh, Sayantani; Lippa, Carol
Idiopathic normal pressure hydrocephalus (iNPH) is a communicating hydrocephalus, of unknown pathophysiology, characterized by the classical triad of dementia, urinary incontinence, and ataxia. The most popular treatment option is shunt surgery, although it is not a cure. The diagnosis of the disorder is challenging as it may mimic a lot of other neurological conditions and has no distinct biomarker. It becomes even more challenging as majority of the cases are diagnosed by invasive cerebrospinal fluid (CSF) removal tests. However, a careful history taking, a keen and detailed physical examination, and pertinent imaging studies can lead to an early diagnosis. The gait symptoms respond the most to surgery. The predictors deciding the postsurgical prognosis has been discussed. Improved shunting modalities and novel shunt materials with valve adjustments have improved the precision of the shunting procedures. Still we have lot more to achieve in terms of early diagnosis and definitive management of iNPH.